Nanoemulsion as an Effective Treatment against Human-Pathogenic Fungi - Alexis Garcia (American Society for Microbiology, 2019)
ABSTRACT Infections triggered by pathogenic fungi cause a serious threat to the public health care system. In particular, an increase of antifungal drug-resistant fungi has resulted in difficulty in treatment. A limited variety of antifungal drugs available to treat patients has left us in a situation where we need to develop new therapeutic approaches that are less prone to development of resistance by pathogenic fungi. In this study, we demonstrate the efficacy of the nanoemulsion NB-201, which utilizes the surfactant benzalkonium chloride, against human-pathogenic fungi. We found that NB-201 exhibited in vitro activity against Candida albicans, including both planktonic growth and biofilms. Furthermore, treatments with NB-201 significantly reduced the fungal burden at the infection site and presented an enhanced healing process after subcutaneous infections by multidrug-resistant C. albicans in a murine host system. NB-201 also exhibited in vitro growth inhibition activity against other fungal pathogens, including Cryptococcus spp., Aspergillus fumigatus, and Mucorales. Due to the nature of the activity of this nanoemulsion, there is a minimized chance of drug resistance developing, presenting a novel treatment to control fungal wound or skin infections. IMPORTANCE Advances in medicine have resulted in the discovery and implementation of treatments for human disease. While these recent advances have been beneficial, procedures such as solid-organ transplants and cancer treatments have left many patients in an immunocompromised state. Furthermore, the emergence of immunocompromising diseases such as HIV/AIDS or other immunosuppressive medical conditions have opened an opportunity for fungal infections to afflict patients globally. The development of drug resistance in human-pathogenic fungi and the limited array of antifungal drugs has left us in a scenario where we need to develop new therapeutic approaches to treat fungal infections that are less prone to the development of resistance by pathogenic fungi. The significance of our work lies in utilizing a novel nanoemulsion formulation to treat topical fungal infections while minimizing risks of drug resistance development.